2019
DOI: 10.1111/jpc.14558
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the paediatric foot using footprints and foot posture index: A cross‐sectional study

Abstract: Aim Footprints have long been used as proxy measures of foot morphology, yet there is little consensus regarding footprints versus measures of foot posture, which address foot anatomy directly. Foot posture in children can be a confusing clinical presentation, with previous studies both supporting and refuting the relationship between childhood obesity and flat feet. The aim of this study was to determine the relationship between footprints and foot posture in children. Methods A total of 316 school children (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…The foot parameters used in the study were foot length, foot width, heel width, arch length, 1–5 metatarsal width, and arch index (AI). The AI, which correlated with foot posture and morphology, and notably, with the navicular height, was measured from the subjects’ standing scans and calculated by dividing the length of the foot into three equal portions (minus the toes) and dividing the footprint in the middle third by the total footprint of all three regions [ 26 ]. The reference criteria were as follows: AI ≤ 0.21 indicating high arch, AI ≥ 0.26 suggesting a flat arch, and normal arch lies between 0.21 < AI < 0.26 [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The foot parameters used in the study were foot length, foot width, heel width, arch length, 1–5 metatarsal width, and arch index (AI). The AI, which correlated with foot posture and morphology, and notably, with the navicular height, was measured from the subjects’ standing scans and calculated by dividing the length of the foot into three equal portions (minus the toes) and dividing the footprint in the middle third by the total footprint of all three regions [ 26 ]. The reference criteria were as follows: AI ≤ 0.21 indicating high arch, AI ≥ 0.26 suggesting a flat arch, and normal arch lies between 0.21 < AI < 0.26 [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Foot posture index (FPI) ( Redmond et al, 2008 ) can effectively evaluate foot posture and categorize feet into three types: pronated, neutral, and supinated position, and it has been proven to be a reliable, simple, and economical method compared to conventional measures ( Evans et al, 2003 ), footprints ( Gijon-Nogueron et al, 2020 ), and automatic measurement apparatus ( Ohi et al, 2017 ). Previous studies have suggested that foot posture evaluated by FPI was closely associated with pain, function in KOA patients ( Al-Bayati et al, 2018 ), and a more pronated foot was found in the patients with medial KOA than in healthy subjects ( Abourazzak et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study aimed to investigate and compare the validity and diagnostic accuracy of CA and FPI-6 against radiographic findings as a criterion standard measure to determine flexible flatfoot in adolescents aged 12-18 years. Based upon the aforementioned information and the previous studies, 1,35 the main hypothesis of this study was that FPI-6 is more valid and diagnostically accurate in determining flatfoot in adolescents.…”
Section: Introductionmentioning
confidence: 87%
“…[31][32][33] FPI-6 has been validated in adults 34 and Paediatric population. 14 Gijon-Nogueron et al, in 2019 35 had concluded that compared with FPI-6, CA overestimates and misguides paediatric foot posture, while other researchers found CA to be a practical, reliable, and sensitive measure. 15,20,36,37 However, the diversity of the methodologies used and the circumstances for each study makes comparisons between the results of these previous studies difficult, leading to an ongoing debate among researchers and clinicians.…”
Section: Introductionmentioning
confidence: 99%